Non-native English-speaking applicants and the likelihood of physician assistant program matriculation - Shahpar Najmabadi; Virginia Valentin; Joanne Rolls; Mary Showstark; Leigh Elrod; Carey Barry; Adam Broughton; Michael Bessette; Trenton Honda (Medical Education Online)
Purpose Effective communication is critical in patient care. Multilingual medical providers, including Physician Assistants (PAs) can contribute to improved health care among patients with limited English proficiency; however, this is contingent upon matriculating multilingual providers. In this study, the association between prospective applicants’ self-reported English as second language (ESL) status and their likelihood of matriculation into a PA program was investigated.Methods Participants included applicants to five admission cycles of the Centralized Application Service for Physician Assistant from 2012 to 2020. Logistic regression was utilized to investigate association between applicant ESL status and odds of program matriculation in both bivariate and multivariable regression models. Models were adjusted for citizenship status, undergraduate grade point average, gender, age, race/ethnicity, number of programs applied to, and patient care hours.Results In unadjusted and adjusted models, ESL status was associated with a significantly lower odds of matriculation to a PA program across all study years. In adjusted multivariable models, associations were strongest for 2014–2015 where ESL status was associated with a 35% lower odds of matriculation (odds ratio 0.65, 95% confidence interval 0.56, 0.76) when controlling for demographics, citizenship status, patient care experience, and academic achievement. In sensitivity analyses restricting to (a) those with TOEFL scores ≥ 100, and (b) restricting to those ESL applicants without TOEFL scores, we did not observe important changes in our results.Conclusions Results indicated that non-native English-speaking applicants have lower odds of PA program matriculation. Decrements in matriculation odds were large magnitude, minimally impacted by adjustment for confounders and persistent across the years. These findings suggest that PA program admission processes may disadvantage non-native English-speaking applicants. While there are potential explanations for the observed findings, they are cause for concern. Matriculating and training PAs who have language concordance with underserved populations are important means of improving patient outcomes.